2022
DOI: 10.1007/s11027-021-09992-z
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry and reforestation with the Gold Standard-Decision Analysis of a voluntary carbon offset label

Abstract: Voluntary standards can help to ensure the quality of projects eligible for carbon offsetting, i.e., selling carbon certificates. However, in deciding on whether to adopt such standards, the managers of carbon offset projects are faced with uncertainty regarding the costs and risks involved. Decision Analysis provides a helpful set of tools that can support such decisions by forecasting outcomes under different scenarios. We applied Decision Analysis methods to generate models for the decisions to certify two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
3
4
0
Order By: Relevance
“…The height, diameter, basal area and volume of Gamhar after completing 12 years was lower under sole plantation compared to agri-silvicultural system 16 . Similar results have also been confirmed by 17 observed that the cash flow analysis of the carbon trading neutral products reported substantial initial investments during the first 3 years of the project, while benefits are obtained after completing 4 years. Kumar et al 18 reported that the total tree biomass (3.707 t ha −1 ), carbon stock (1.597 t ha −1 ), carbon sequestration (5.862 t ha −1 ), carbon credit (5.86) and carbon price ($ 103.76) respectively were estimated at the age of two years of poplar tree-based agroforestry system.…”
Section: Discussionsupporting
confidence: 81%
“…The height, diameter, basal area and volume of Gamhar after completing 12 years was lower under sole plantation compared to agri-silvicultural system 16 . Similar results have also been confirmed by 17 observed that the cash flow analysis of the carbon trading neutral products reported substantial initial investments during the first 3 years of the project, while benefits are obtained after completing 4 years. Kumar et al 18 reported that the total tree biomass (3.707 t ha −1 ), carbon stock (1.597 t ha −1 ), carbon sequestration (5.862 t ha −1 ), carbon credit (5.86) and carbon price ($ 103.76) respectively were estimated at the age of two years of poplar tree-based agroforestry system.…”
Section: Discussionsupporting
confidence: 81%
“…The height, diameter, basal area and volume of Gamhar after completing 12 year was lower under sole plantation compared to agri-silvicultural system 32 . Similar results have also been con rmed by 33 observed that the cash ow analysis of the carbon trading neutral products reported substantial initial investments during the rst 3 years of the project, while bene ts are obtained after completing 4 year. 34 reported that the total tree biomass (3.707 t ha − 1 ), carbon stock (1.597 t ha − 1 ), carbon sequestration (5.862 t ha − 1 ), carbon credit (5.86) and carbon price ($ 103.76) respectively were estimated at the age of two years of poplar tree based agroforestry system.…”
Section: Discussionsupporting
confidence: 81%
“…It would ensure the standardized quality of carbon credits, market credibility, and buyer confidence (Ziegler, 2023). Further, it would check for overinflated emission baselines and dubious carbon credits (Netter et al, 2022), as noted in an article by West et al (2020) about worthless rainforest REDD + carbon credits.…”
Section: Evolution Of Carbon Markets and Creditsmentioning
confidence: 99%